Application Of Industrial Revolution 4.0: An Overview On Biodegradable Polymer Production - et. al., Tang Tung Hau, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Industry revolution 4.0 represents the future technological capability of an industry that can be achieve through extensive research on linking digital database with mechanical equipment. This initiative is primarily designed to digitize the structure of the manufacturing process, allowing the control on variables in a plant and also improve accessibility of crucial information that is useful for operators to improve the performance of the process. Some examples of Industrial Revolution 4.0 technologies are Smart Equipment, drone with high resolution cameras and predictive sensors, all linked through the Internet of Things (IOT), allowing access into the massive data, churned out by intricate software, which operators can analyze to implement suitable solutions based on the feedback. This paper also presents how the process of producing biodegradable polymer can benefit should if Industrial Revolution 4.0 is implemented. Also, the contribution and skills required by chemical engineers to practice Industrial Revolution 4.0 is discussed. This paper mainly represents an overview on how Industrial Revolution 4.0 affects the industry market and what engineers need to navigate through this new era.